Respostas

2013-08-03T10:47:07-03:00
O)(6x)2+x-1=0
    12x+x=0+1
         13x=1
             x=1
                13

P) (3x)2-7x+2=0
      6x-7x=-2
          -x=-2(multiplica por -1)
            x=2

Q) (2x)2-7x=15
        4x-7x=15
          -3x=15 (multiplica por -1)
             x=-15
                  3
             x=-5


R)(4x)2+9=12x
    8x-12x=-9
        -4x=-9 (multiplica por -1)
         4x=9
           x=9
               4
             

S)x2=x+12 (eu entendi que x2 é x²)
   x²-x-12=0
a=1
b=-1
c=-12

Delta=-1²-4*1*-12
Delta=1+48
Delta=49

x'=-(-1)+V49/2*1
x'=1+7/2
x'=8/2
x'=4

x''=-(-1)-V49/2*1
x''=1-7/2
x''=-6/2
x''=-3

 
T)(2x)2=-12x-18
    4x+12x=-18
         16x=-18
             x=-18 (simplifica por 2)
                  16         
             x=-9
                  8


U)x2+9=4x (Entendi que x2 é x²)
   x²+9=4x
   x²+9-4x=0
   x²-4x+9=0
a=1
b=-4
c=9


Delta=(-4)²-4*1*9
Delta=16-36
Delta=-20

Como Delta é negativo então esta equação não possui raízes reais.